The impact of credibility of streamers on the acceptance of live streaming commerce: An extended UTAUT model - Ng, Alex Hou Hong; Wider, Walton; Ho, Ree Chan; Wong, Chee Hoo; Ngui, Kwang Sing; Bien, Jonna Karla (Asian Development Policy Review, 2024)
This study aims to explore how innovation adoption, based on the Unified Theory of Acceptance and Use of Technology (UTAUT), influences online shopping through live streaming platforms. It focuses on understanding the factors that drive customer acceptance and usage behavior in the context of live streaming commerce. The research employed a quantitative methodology, utilizing a survey instrument to collect data. The participants comprised 237 online customers in Malaysia who were familiar with live streaming as a shopping medium. The SmartPLS software, which is a tool for structural equation modelling, was utilized for data analysis. The findings suggest that performance expectation, effort expectancy, and social influence, which are important components of the UTAUT theory, have a considerable impact on consumer acceptance and usage behaviour in live streaming commerce. Additionally, the credibility of streamers emerged as a critical factor influencing purchase intentions. These findings highlight the importance of streamer credibility in the live streaming shopping experience. This research offers valuable insights for online retailers and businesses utilizing live streaming platforms for commerce. Understanding the factors that encourage customer engagement and purchase can help in strategizing marketing and operational approaches. It also suggests that the streamers' credibility is a vital aspect of the shopping experience, pointing towards the need for selecting and training streamers effectively. Moreover, this study extends the applicability of the UTAUT theory to live streaming commerce, providing a framework for further research in this emerging field.